Analisis Kinerja Pegawai dengan Komitmen Organsisasi pada DISPORA Provinsi Sumatera Barat - Meswantri .; Moh. Taufan Nugroho (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Organizational commitment is one of the key factors influencing employee performance in the public sector, including government institutions such as the Youth and Sports Office (DISPORA). In an era of increasing demands for public service quality, government organizations are required to deliver services that are effective, efficient, and accountable. To achieve these objectives, human resources must possess not only the necessary competencies but also a strong commitment to the organization. This study aims to analyze the extent to which the work environment, organizational culture, and work discipline influence employee performance, with organizational commitment serving as an intervening variable at the Youth and Sports Office of West Sumatra Province. The analytical technique employed was Structural Equation Modeling (SEM) based on SmartPLS. Data were collected through a survey method by distributing questionnaires to 94 respondents. The findings indicate that the work environment, organizational culture, and work discipline each have a significant effect on organizational commitment. However, the work environment and organizational culture do not have a significant direct effect on employee performance, whereas work discipline has a significant effect on employee performance. Furthermore, organizational commitment is found to have a significant effect on employee performance. The indirect effect analysis reveals that the work environment does not significantly influence employee performance through organizational commitment. In contrast, organizational culture and work discipline significantly affect employee performance through organizational commitment as a mediating variable. These findings confirm that organizational commitment plays an important mediating role, particularly in strengthening the influence of organizational culture on employee performance.